Removal of oil from oil-water emulsion by hybrid coagulation/sand filter as pre-treatment - Daniel Johnson (Journal of Water Process Engineering, 2018)
The removal of oil from water is of increasing importance in many industries, such as oil and gas, petrochemical and food industries, because of the large volumes of oily wastewater they produce. The aim of this work is to evaluate and compare the performance of ferrous and aluminium sulfate coagulations and to compare between sand filter, coagulation and a hybrid coagulation/sand filter process when used as pre-treatment options. When the concentration of oil was low in the oil-water emulsion, the treatment by sand filter alone was adequate (oil ≤ 50 mg/L). On the other hand, when the oil concentration was greater than 50 mg/L, advanced treatments such as coagulation are required as post-processes to reach good water quality. Aluminium sulfate was observed to be more efficient (about 5% to 7% higher than the use of ferrous sulfate) and less costly than ferrous sulfate to remove oil from oil-water emulsion using coagulation. The optimal technology for pre-treatment to remove oil from oil-water emulsion was found to be a coagulant dosage of aluminium sulfate combined with sand filter at pH 8 during various concentrations as hybrid. Optimal conditions were found to occur at mixing duration and speed of 120s and 250 rpm respectively.